Biomedical equipments, vaccine and drug in the prevention, diagnosis and treatment of COVID-19 - Ling Zhang (Heliyon, 2023)
SARS-CoV-2 virus caused an infectious disease, named COVID-19. Biomedical equipments, vaccine and drug have played a crucial role in the prevention, diagnosis and treatment. Nevertheless, up to now, there still has been no literature summarizing the diagnosis, prevention and treatment of this infectious disease from the perspective of biomedical equipments. Thus, this review wants to give an overview on the biomedical equipments, vaccine and drug in the prevention, diagnosis and treatment of this disease, and avoids the overlap with previous research, more emphasis on biomedical equipments, and less emphasis on biomaterials. The existing problems in the current research and application were summarized, and the future research direction was proposed, so as to provide reference to deal with similar viral infections in the future.